Entrepreneurial intention theory in Malaysian communities: A concept paper - Abu Seman, Shahri; Amborashang, Jumain (Jurnal Evolusi, 2023)
This study aims to refine and contextualize existing models of entrepreneurial intention by examining how internal and external factors shape entrepreneurial intentions within Malaysian communities. Recognizing that entrepreneurship is largely an intentional and planned behavior, this research evaluates the applicability of two widely referenced intention models—the Theory of Planned Behavior (Ajzen, 1991) and the Entrepreneurial Event Model (Shapero, 1982)—within Malaysia’s unique sociocultural context. While prior research often emphasizes personality traits or demographic predictors, these factors have shown limited predictive power, particularly in diverse cultural settings. Instead, this study focuses on the dynamic interaction between personal attitudes, self-efficacy, perceived feasibility, and culturally specific external influences such as family expectations, community norms, and institutional support. Given Malaysia’s multicultural society and varied economic policies, understanding these interactions is crucial for developing effective, localized strategies to foster entrepreneurship. By comparing intention models and integrating them with Malaysia-specific variables, this research seeks to enhance predictive accuracy and provide practical insights for educators, policymakers, and entrepreneurship support programs. The findings are expected to contribute to the development of more culturally responsive frameworks, promoting sustainable entrepreneurial ecosystems in Malaysia and offering a basis for comparative studies in other emerging economies with similar sociocultural complexities